Creep-ratcheting behavior of PTFE gaskets under various temperatures. (July 2017) - Zheng, Xiaotao; Wen, Xiang; Wang, Wei; Gao, Jiuyang; Lin, Wei; Ma, Linwei; Yu, Jiuyang
Abstract: Compressive creep-fatigue experiments on PTFE gaskets with small stress amplitude were tested. The effects of peak holding times and temperatures on creep-ratcheting behaviors were further discussed. Results showed that at room temperature, the accumulated creep-ratcheting strain corresponding to 400 cycles for peak holding 1min is nearly 1.06 times that for peak holding time 0.5min and 1.3 times that without peak holding. While, at 100 °C, 150 °C and 200 °C, they are almost 1.1 times and 1.6 times, 1.1 times and 1.7 times, 1.05 times and 1.9 times, respectively. This means although the accumulated creep-ratcheting strains for peak holding 0.5min and 1min are very close to each other, but short peak holding time still has obvious effect on the accumulated deformation comparing that without peak holding. Moreover, the creep-ratcheting deformation with short peak holding time and small stress amplitude for PTFE gaskets can be simply estimated by the corresponding compressive static creep strain at the same peak stress in practical engineering with relatively good accuracy.